Ethical and regulatory guidelines in clinical trials of xenocorneal transplantation in Korea; the Korean xenocorneal transplantation consensus statement. (20th May 2013) - Kim, Mee Kum; Lee, Jong Joo; Choi, Hyuk Jin; Kwon, Ivo; Lee, HyungKeun; Song, Jong‐Suk; Kim, Myoung Joon; Chung, Eui‐Sang; Wee, Won Ryang; Park, Chung‐Gyu; Kim, Sang Joon
Abstract: Background: To establish the consensus about the conditions for undertaking clinical trials in xenocorneal transplantation in Korea, specific issues regarding the xenocorneal transplantation on ethical and regulatory aspects are addressed, and the guidelines to conduct clinical trial of the xenocorneal transplantation are proposed. Method and Results: Chapter 1 reviews the key ethical requirements and progress of a Korean regulatory framework for clinical trials of xenocorneal transplantation. Chapters 2–7 provide recommendations on source pigs, quality control of porcine corneal procurement, preclinical efficacy required to justify a clinical trial, strategies to prevent transmission of porcine endogenous retrovirus (PERV), patient selection for clinical trials, and informed consent in xenocorneal transplantation using either cellularized or decellularized porcine graft, which are essentially based on the International Xenotransplantation Association (IXA) islet xenotransplantation consensus statement. The consensus statement of the inclusion criteria for the patients' selection has been made by the executive board members in Korean External Eye Disease Society. Conclusions: This consensus statement will be a good initiative for Korean Food and Drug Administration to discuss final regulatory guidelines in conducting clinical trials of xenocorneal transplantation in Korea and for International Xenotransplantation Association to develop International Consensus Standards of Xenocorneal Transplantation.